Awareness and Utilization of Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (AB-NHPM) among Beneficiaries of Gautam Buddha Nagar District: A Comparative Study - Raghav Dixit; Ambren Chauhan; Khushboo Juneja (Indian Journal of Community Medicine)
Ayushman Bharat scheme is a National Health Protection Scheme introduced on September 23, 2018 by the government of India. The study was done to estimate the awareness and utilization of the Ayushman Bharat scheme in the urban and rural beneficiaries of Gautam Buddha Nagar. A comparative cross sectional study was conducted in the field practice areas of the Department of Community Medicine, Gautam Buddha Nagar, Uttar Pradesh among 224 households. Simple random sampling was done, and data was collected using a semi-structured questionnaire. Our study found that around 8.9% and 18.8% of beneficiaries in urban and rural areas, respectively were aware of the benefits of the scheme. The study also reported that only 8% of beneficiaries in urban areas have utilized the benefits of the scheme while 15.2% of beneficiaries in rural areas have utilized the benefits in rural area. Creating good awareness campaigns, special drives, and working toward quality assurance in both the public and private sectors will help beneficiaries get the best out of this dynamic healthcare scheme.